[Math] Convolution of two sums (Fourier transform)

convolutionfourier analysis

This question is from the book "Advanced Engineering Mathematics" by Stroud.

Question

I can't seem to get the required answer for this. I've derived the two Fourier transform equations for them.

Transform
.

U and V are dummy variables.

I've been told I need to use the convolution theorem by multiplying the functions in the frequency domain and finding the inverse transform of the solution, but I don't know how to proceed with the equations I've got.

Best Answer

The Fourier transform is a linear operator, so

$$ F_1(\omega) = \sum_{n=-\infty}^{\infty} c_n \mathcal{F}(e^{jn\omega_0 t}) = \sum_{n=-\infty}^{\infty} c_n \delta( \omega-n\omega_0) $$

Use the above to multiply the two Fourier transforms. Then see if you can take the take the inverse transform to finish the proof.

EDIT:

To see how to find the product of the two sums note that

$$ \delta( \omega - n \omega_0) \cdot \delta( \omega - m \omega_0) \neq 0 \Leftrightarrow n = m. $$

Furthermore,

$$ m=n \Rightarrow \delta( \omega - n \omega_0) \cdot \delta( \omega - m \omega_0) = \delta( \omega - n \omega_0) = \delta( \omega - m \omega_0). $$

Thus,

$$ d_m \delta( \omega - m\omega_0) \cdot \sum_{n=-\infty}^{\infty} c_n \delta( \omega-n\omega_0) = d_m \delta( \omega - m\omega_0) \cdot c_m \delta( \omega - m\omega_0) = d_m c_m \delta( \omega - m\omega_0) $$

EDIT 2:

We know that

$$ F_1(\omega) = \sum_{n=-\infty}^{\infty} c_n \delta( \omega-n\omega_0) $$

$$ F_2(\omega) = \sum_{m=-\infty}^{\infty} d_m \delta( \omega-m\omega_0) $$

Their product is then

$$ F_1 (\omega) F_2 (\omega) = \left( \sum_{n=-\infty}^{\infty} c_n \delta( \omega-n\omega_0) \right) \left( \sum_{m=-\infty}^{\infty} d_m \delta( \omega-m\omega_0) \right) $$

By the definition of the Dirac delta function, we know that

$$ \delta(\omega - a) \cdot \delta( \omega - b) = \left\{ \begin{array}{lr} \delta(x-a), & a = b \\ 0, & a \neq b \end{array} \right. $$

Thus, if we consider an individual term in the series $F_1 (\omega)$ by fixing $n$ and take its product with $F_2(\omega)$, we get

$$ c_n \delta(\omega - n\omega_0) \left( \sum_{m=-\infty}^{\infty} d_m \delta( \omega-m \omega_0) \right) = c_n d_n \delta(\omega - n\omega_0). $$

Since this is true for all $n$, we have that

$$ F_1 (\omega) F_2 (\omega) = \sum_{n=-\infty}^{\infty} c_n d_n \delta( \omega-n \omega_0). $$

Related Question